2020
DOI: 10.1097/shk.0000000000001709
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Syndecan-1 and Tissue Factor Pathway Inhibitor, Biomarkers of Endothelial Dysfunction, Predict Mortality in Burn Patients

Abstract: Objective: The aim of this study is to evaluate the association between burn injury and admission plasma levels of Syndecan-1 (SDC-1) and Tissue Factor Pathway Inhibitor (TFPI), and their ability to predict 30-day mortality. Background: SDC-1 and TFPI are expressed by vascular endothelium and shed into the plasma as biomarkers of endothelial damage. Admission plasma biomarker levels have been associated with morbidity and mortality in trauma patients, but this has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…We found that the anticoagulant activity of TFPI in trauma patients was significantly higher than that in healthy controls, a finding consistent with the results of Keyloun's study. 13 The reason for the increased anticoagulant activity of TFPI in patients with trauma may be related to extensive injury of vascular endothelial cells and inflammation caused by traumatic fractures. There is no doubt that traumatic fracture as an external force leads to endothelial cell activation and injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the anticoagulant activity of TFPI in trauma patients was significantly higher than that in healthy controls, a finding consistent with the results of Keyloun's study. 13 The reason for the increased anticoagulant activity of TFPI in patients with trauma may be related to extensive injury of vascular endothelial cells and inflammation caused by traumatic fractures. There is no doubt that traumatic fracture as an external force leads to endothelial cell activation and injury.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that full-length TFPI in plasma may be a marker of endothelial cell dysfunction. Basic experiments carried out by Zhao et al 30 found that TFPI can reduce endothelial cell injury by inhibiting endothelial autophagy and the class III PI3K/Beclin-1 pathway, while in clinical studies, Keyloun et al 13 used TFPI as a biomarker of endothelial injury and showed that the high level of TFPI in burn patients was related to a nine-fold increase in mortality (OR:9.59), and provided a predictive index of burn mortality. On the other hand, the inflammation caused by trauma has always been the focus of research attention, with studies showing that the levels of pro-inflammatory factors in plasma of post-traumatic patients were increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a new perspective on other research to understand the interaction between glycocalyx and neutrophils [ 8 ]. Other studies have shown that glycocalyx dysfunction may be associated with vascular leakage due to burns [ 9–13 ]. This suggests that there may be different interactions between neutrophils and glycocalyx in different disease settings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that burn and nonburn trauma patients with high admission SDC-1 levels experience increased morbidity and mortality. 20 , 21 Concomitant IHI probably contributes to the presence and severity of endotheliopathy and coagulopathy in burns. The objective of this study was to examine the association between IHI, endothelial dysfunction, coagulation homeostasis, and clinical outcomes.…”
mentioning
confidence: 99%